Recommendations to Improve the Influenza Immunization Rates of Respiratory Healthcare Professionals: A Survey Conducted in Puerto Rico - Coppola-Fasick, Giannina; González-Sepúlveda, Lorena; Arce-Ayala, Yanira; Ramos-Romey, Cristina; Nazario, Sylvette (Puerto Rico Health Sciences Journal, 2023)
Objective: Influenza affects 5–15% of the worldwide population and is responsible for 4–5 million cases and 250,000–500,000 deaths. Despite established recommendations, vaccination rates continue to be low. Our study aimed to identify barriers to influenza immunization and attitudes toward the vaccine among respiratory health care (HC) professionals in Puerto Rico. Methods: We conducted an anonymous written survey that was handed out to 130 HC professionals, including physicians, nurses and respiratory therapists, who attended the Annual Respiratory Disease Congress held in San Juan, Puerto Rico, on August 2018. Results: A total of 68 health care professionals participated in the study. Nearly 34% of participants reported never receiving influenza immunization themselves, 13% reported intermittent immunization, and 53% received immunizations yearly. Approximately 82% and 87% of the participants believed the influenza vaccine to be safe and effective, respectively. Sixty- five percent of respiratory therapists considered the vaccine effective, as compared to 94% of physicians and 100% of nurses and other HC professionals (p=0.023). Most of the participants (87%) recommended influenza immunization, although 38% of participants indicated being concerned about potential side effects of the vaccine. Knowledge of current clinical indications for influenza immunization for medical conditions varied from 59% for patients on systemic steroids to 94% for patients with diabetes mellitus. Conclusion: This survey among respiratory HC professionals in Puerto Rico demonstrated barriers in knowledge about vaccination, its indications, and its safety. Addressing these barriers provides us with opportunities to improve influenza immunizations rates among HC workers and their patients.